Guidance Teacher Interpersonal Communication Patterns Counseling in Handling Violations Discipline in Students) - Ramdan, Deden; Sophia, Evie (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2023)
This study has a discussion of how interpersonal communication patterns that occur between counseling teachers and students in dealing with disciplinary violations. The purpose of this study is to find out how the communication patterns carried out by counseling teachers who focus on interpersonal communication occur in counseling guidance teachers and students in dealing with disciplinary violations at SMK Islam Iqro Pasarkemis. The research method used by researchers in this study is a qualitative method with a qualitative descriptive study approach. Data collection was conducted through field observations and interviews, as well as documentation. There are twenty-two people as informants, including one expert informant, one academic informant, and twenty students as supporting informants. The results of this study show that the communication that occurs between guidance and counseling teachers with students is formed from self-concepts built by each individual and acts on their respective meanings. Guidance and counseling teachers and students understand each other's objects, so that from the interaction that occurs between guidance and counseling teachers with students